Ja-Ty-Wspólnota. Samotność jako strategia wykluczania? - Kulig, Agnieszka (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2014)
In the article I reconstruct the psychological structure of solitude. The two forms of solitude – by choice and unwanted – influence the way of experiencing and describing it in culture. I analyze the unwanted solitude, imposed on individuals and communities sources of which are cultural differences, power of stereotypes and superstitions. The violence against ethnic and religious minorities can appear where there is an approval of maintaining cultural solitude. I also consider the relationship between the concept of solitude and Bernhard Waldenfels' alienation category.